2011
DOI: 10.2176/nmc.51.740
|View full text |Cite
|
Sign up to set email alerts
|

Rathke's Cleft Cyst With Xanthogranulomatous Change -Case Report-

Abstract: Fig. 1 Computed tomography scans showing a solid intrasellar lesion appearing isodense with rod-like calcification (arrow). AbstractA 58-year-old man presented with a rare case of Rathke's cleft cyst (RCC) manifesting as headache and visual disturbance. Goldman's perimeter showed he had bitemporal hemianopia. Magnetic resonance imaging revealed a solid intrasellar lesion. He underwent surgery via a right pterional approach. The lesion was red, solid, and fibrous. Histological examination revealed a few colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Although some theories have been proposed, the pathogenesis of XGI remains largely unknown. The content of a ruptured cyst and cyst epithelium in contact with the surrounding tissue have been suggested to cause XGI through various mechanisms including activation of monocytes/macrophages [17][18][19]. Similar to the presented case, patients with ruptured Rathke' cleft cyst also result in reactive xanthogranulomatous hypophysitis.…”
Section: Discussionsupporting
confidence: 71%
“…Although some theories have been proposed, the pathogenesis of XGI remains largely unknown. The content of a ruptured cyst and cyst epithelium in contact with the surrounding tissue have been suggested to cause XGI through various mechanisms including activation of monocytes/macrophages [17][18][19]. Similar to the presented case, patients with ruptured Rathke' cleft cyst also result in reactive xanthogranulomatous hypophysitis.…”
Section: Discussionsupporting
confidence: 71%
“…Then in 1999, Paulus et al suggested that sellar xanthogranuloma is clinically and pathologically distinct from the classical adamantinomatous craniopharyngioma (2). According to a study published in 2011, the incidence of intracranial xanthogranuloma is 1.6-7%, and lesions are only rarely found in the sellar and parasellar regions (5). Of the 643 patients with sellar or parasellar tumors retrospectively reviewed by Rahmani et al only 4 patients (0.6%) had histologically confirmed xanthogranulomas (6).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[14][15][16]20,25,26 Hence, the incidence of xanthogranulomas in Western countries is unclear. Likewise, the management of these lesions has been almost universally through craniotomy or microscopic transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,21 Many authors have described the presentation of endocrine, visual, and neurological manifestations in parasellar xanthogranulomatous reactions, but a unique symptomatology has not yet been elucidated. 1,2,[6][7][8]12,15,16,20,21,23,[25][26][27] Furthermore, there is significant controversy regarding the etiology and development of these unusual lesions. One theory of the etiology of these parasellar lesions is that all xanthogranulomas arise from inflammatory processes occurring in preexisting CPs.…”
Section: Discussionmentioning
confidence: 99%